FLOCCULAR SYNDROME- AN ATYPICAL PRESENTATION OF PARANEOPLASTIC CEREBELLAR DEGENERATION - Saba Zaidi,; Haneea Yasir ,; Ayesha Jaka, (Journal of Ayub Medical College Abbottabad, 2024)
The flocculus, a small and distinct region of the cerebellum, plays a crucial role in coordinating eye movements, especially in stabilizing visual images on the retina during head movements. Damage or lesions in the flocculus can lead to a specific neurological syndrome called floccular syndrome. This syndrome is characterized by abnormalities in the vestibulo-ocular reflex (VOR), which helps coordinate eye movements with head movements to maintain clear vision. Progressive ataxia, particularly affecting the flocculus, combined with vestibulo-ocular reflex abnormalities, strongly suggests the presence of paraneoplastic cerebellar degeneration. In our case study, we described the clinical presentation of a middle-aged woman who experienced gradually worsening dizziness and ocular issues. Due to the subacute onset of cerebellar symptoms and normal neuroimaging evidence of cerebellar atrophy, we initiated a paraneoplastic workup, revealing positive anti-Yo antibodies. This prompted consideration of the diagnosis of PCD with floccular syndrome. The patient underwent steroid therapy, resulting in partial symptom improvement. Despite thorough investigations for hidden malignancies, no occult tumour was found. Our case report aims to underscore the rare and distinct features of PCD, as observed in this particular patient.